Latinas in the Criminal Justice System: Victims, Targets, and Offenders - Báez, Johanna; Camacho, Ariana; Cano, Veronica; Cepeda, Alice; Cervantes, Andrea; Denious, Jean; Dingeman, Katie; Durfee, Alesha; Escamilla, Heriberto; Escobar, Martha; Flores, Jerry; Foster, Holly; et al. (Latina/o Sociology, 2021)
Frontmatter -- Contents -- Introduction -- Contributors -- Part I. Victimization to Offending: Blurring the Boundaries -- 1. Entre Mujeres Platicamos: The Role of Informal Social Networks among Latina Survivors of Intimate Partner Violence -- 2. Latina Interpersonal Victimization: The Importance of Sexual Orientation -- 3. Nondisclosure of IPV Victimization among Disadvantaged Mexican American Young Adult Women -- Part II. Latina Offenders from Court to Correctional Involvement -- 4. Demasiados Problemas: A Focus on Gender, Ethnicity, and Juvenile Diversion Programming -- 5. On the Run and In/Out of the System: Understanding Latina Girls in a Southern California Barrio -- 6. The Correlates and Consequences of Maternal Efficacy among Imprisoned Women -- Part III. Immigration Enforcement, Crimmigration, and the Deportation Machine -- 7. No Solamente Porque Soy Mujer: A Transnational Intersectional Framework for Understanding Latin American Women’s Experiences with Crimmigration -- 8. Masking Punitive Practices: Latina Immigrants’ Experiences in the U.S. Detention Complex -- 9. Adriana and Esther: Experiences of Formerly Incarcerated Migrant Women Deportees -- 10. Young Women’s and Girls’ Experiences in the Facilitation of Migrant Smuggling -- Part IV. Community Programming for System- Impacted Latinas -- 11. From the Streets to the Halls of Higher Education: The Case of an Undocumented Latina on the Margins of the Justice System -- 12. Maternal Racial and Ethnic Strategies as a Protective Factor against Delinquency among Latina Girls: An Exploratory Study -- 13. Mi Hermana’s Keeper: Empowering Latina Youth to Improve Services That Prevent Juvenile Justice System Involvement -- 14. Xinachtli: A Healing- Informed, Gendered, and Culturally Responsive Approach with System- Involved Latinas -- Conclusion -- About the Contributors -- About the Editors -- Index